Essentials of diagnosis & treatment for PDA - Tierney, Lawrence M.; Saint, Sanjay; Whooley, Mary A. (New York : Mc Graw-Hill, 2002)
Quick answers to questions about the 500 most common medical disorders
Mc Graw-Hill Mobile Consult
System requirements PALM: Handheld Device: Palm OS 3.x or later 77ok of available memory. Memory cards not supported Desktop Computer: Windows OS 95, 98, ME, 2000, XP, or NT 4.0 Workstation (SP3). HotSync Manager (or equivalent), version 3.01 or later. Connection to the Internet POCKET PC: Handheld Device:Win CE 3.0 or above (e.g., Pocket PC 2000, Pocket PC 2002, or above). A strongARM processor. 1.1 MB of available memory. Memory. Memory cards are supported Desktop Computer: Windows OS 95, 98, ME, 2000, XP, or NT 4.0 Workstation (SP3). ActiveSync 3.1 or later. Connection to the internet.
Keywords: Diagnosis -- CD-ROM; Therapeutics -- CD-ROM; Internal medicine